2014
DOI: 10.1371/journal.pntd.0003209
|View full text |Cite
|
Sign up to set email alerts
|

Public Awareness and Knowledge of Neglected Tropical Diseases (NTDs) Control Activities in Abuja, Nigeria

Abstract: The need to engage the public in Neglected Tropical Diseases (NTDs) control activities has become imperative in the context of morbidity reduction through preventive chemotherapy and community participation. Therefore, a survey was conducted among the general public to assess their knowledge and awareness of NTDs control activities in Nigeria. A simple questionnaire was administered to the general public attending a job fair in Abuja, Nigeria. Of the 461 respondents, a significant proportion 337 (73.1%) have h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 8 publications
9
17
0
Order By: Relevance
“…In the current study, the students themselves perceived a gap in the public awareness regarding NTDs where nearly half of them agreed on the low level of public awareness regarding these diseases in Egypt. On the other hand, a study done in Nigeria to assess the general citizen's knowledge and awareness of NTDs control activities found that a significant proportion of the included subjects (73.1%) have heard of NTDs before, yet only 63.1% have good knowledge about them [23]. Lemoine and colleagues stated that the adherence to management guidelines was positively associated with the population's awareness and understanding of the disease, its modes of transmission, mass drug administration campaign, expected adverse effects, and the subject's perception about the risk of infection [24].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 97%
“…In the current study, the students themselves perceived a gap in the public awareness regarding NTDs where nearly half of them agreed on the low level of public awareness regarding these diseases in Egypt. On the other hand, a study done in Nigeria to assess the general citizen's knowledge and awareness of NTDs control activities found that a significant proportion of the included subjects (73.1%) have heard of NTDs before, yet only 63.1% have good knowledge about them [23]. Lemoine and colleagues stated that the adherence to management guidelines was positively associated with the population's awareness and understanding of the disease, its modes of transmission, mass drug administration campaign, expected adverse effects, and the subject's perception about the risk of infection [24].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 97%
“…As well as effective engagement with health decision makers at regional and national levels, there is strong evidence linking the success of disease interventions to engagement with local communities to engender trust in outcomes and hence productive participation [26–28]. A major barrier to improving the treatment of SBE is the perception across many LMIC communities that rather than being a physical illness amenable to medical treatment, snakebites, like many other unexpected illnesses, are associated with deity punishment, witchcraft, or other powerfully persuasive phenomena that are often very locally specific [29, 30].…”
Section: Empowering and Engaging Communitiesmentioning
confidence: 99%
“…Although the Nigerian government in recent times has scaled up efforts on control of schistosomiasis and other NTDs, funds allocation to these diseases are not adequate [ 25 ]. Among the NTDs, schistosomiasis is even more neglected, especially in terms of public awareness [ 26 ]. Several international organisations and NGOs have come to the rescue over the years.…”
Section: Progress In Schistosomiasis Control In Nigeriamentioning
confidence: 99%
“…Despite schistosomiasis being the most studied NTD in Nigeria [ 34 ], a report of 21.5% level of awareness about schistosomiasis specific control activities is very low. This is unlike onchocerciasis where public awareness about control programmes seemed to be high [ 26 ]. The reason alluded to this encouraging awareness level about onchocerciasis is the fact that onchocerciasis control activities in Nigeria have been ongoing since 1991 [ 35 ] unlike that of schistosomiasis that began much more later.…”
Section: Current Challenges In Schistosomiasis Control In Nigeriamentioning
confidence: 99%